Swim specialty effects energy cost and motor organization - Seifert, L.; Komar, J.; Lepretre, P.-M.; Lemaitre, F.; Chavallard, F.; Alberty, M.; Houel, N.; Hausswirth, C.; Chollet, D.; Hellard, P. (International Journal of Sports Medicine, 2010)
The purpose of this study was to analyse the effect of swimmer specialty on energy cost and motor organization. The stroking parameters (velocity, stroke rate, stroke length, stroke index) and the index of coordination (IdC) of 6 elite sprinters were compared with those of 6 elite long-distance swimmers during an incremental swimming exercise test (6×300 m separated by 30 s of passive recovery) that progressively increased the energy cost. Energy cost (C), with its aerobic (Caero) and anaerobic (Canaero) components, was determined by measuring oxygen uptake (VO2) and blood lactate ([La]). Motor organization was assessed by analysis of video recordings from aerial and underwater side-view cameras. The results showed that throughout the test, both groups increased C, Canaero, stroke rate and IdC and decreased Caero and stroke length (all P<0.05). On the mean of the 300-m sets, sprinters had higher values for C (14.8 vs. 12.9 J·kg-1·m-1), Canaero (33.8 vs. 23.4%), [La] (5.9 vs. 3.1 mmol·L-1), stroke length (2.31 vs. 2.28 m) and IdC (-11.2 vs. -21.7%) and lower values for Caero (66.2 vs. 79.6%), VO2 net (2 825 vs. 2 903 mL·min-1), stroke rate (0.55 vs. 0.62 Hz) and stroke index (2.96 vs. 3.19 m2·s-1) than long-distance swimmers (all P<0.05). For the same relative intensity, sprinters accumulated more lactate and swam more slowly than long-distance swimmers; they showed greater change in their arm coordination but their swimming economy was lower.